2006
DOI: 10.1890/0012-9658(2006)87[1094:tuogct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Genetic Clines to Estimate Dispersal Distances of Marine Larvae

Abstract: Many unresolved issues in the ecology and evolution of marine populations center on how far planktonic larvae disperse away from their parents. Genetic tools provide a promising way to define the spatial spread of larvae, yet their accurate interpretation depends on the extent to which genetic loci are under selection. Genetic clines, geographic zones in which genetically differentiated populations interbreed, provide opportunities to explicitly and simultaneously quantify the relative roles of selection and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 73 publications
5
85
0
Order By: Relevance
“…In a related study using several populations of S. purpuratus, Pespeni et al (2013) observed rapid selection of genes encoding proteins involved in calcification under acidification, demonstrating a potential for rapid evolution to occur in this species. Generally, in slowgrowing organisms with long-generation times such as coldwater corals, persistence in a changing ocean will likely hinge on the maintenance of genetic diversity and the success of resilient genotypes, the potential for individual acclimatization, or local adaptation among populations in the presence of both selection and gene flow (Palumbi and Sotka, 2006). While it is unknown if the observed resilience within certain genotypes to climate change stressors in the present study of L. pertusa is heritable, the general consistency in the response of different nubbins of the same genotype within and among different experiments provides evidence for the adaptive capacity of this species.…”
Section: Population and Genotypic Variability In Response To Ocean Acmentioning
confidence: 99%
“…In a related study using several populations of S. purpuratus, Pespeni et al (2013) observed rapid selection of genes encoding proteins involved in calcification under acidification, demonstrating a potential for rapid evolution to occur in this species. Generally, in slowgrowing organisms with long-generation times such as coldwater corals, persistence in a changing ocean will likely hinge on the maintenance of genetic diversity and the success of resilient genotypes, the potential for individual acclimatization, or local adaptation among populations in the presence of both selection and gene flow (Palumbi and Sotka, 2006). While it is unknown if the observed resilience within certain genotypes to climate change stressors in the present study of L. pertusa is heritable, the general consistency in the response of different nubbins of the same genotype within and among different experiments provides evidence for the adaptive capacity of this species.…”
Section: Population and Genotypic Variability In Response To Ocean Acmentioning
confidence: 99%
“…First, most marine bivalve populations are characterised by heterozygote deficiencies at many loci (Wei et al, 2013a). Not only is this 'universal' phenomenon a potential problem in its own right in terms of violating assumptions of many analyses, it may also contribute to difficulties in the detection of linkage disequilibrium (Sotka and Palumbi, 2006). Second, there are no fixed allelic differences that define the two lineages (Wei et al, 2013a).…”
Section: Rationale For Analytical Approachmentioning
confidence: 99%
“…Hybrid zones are barriers to gene flow between parental types and as such can be sigmoidal in shape, describing the transition from one genetic group to the other through a transition zone (Harrison, 1990;Arnold, 1997;Sotka and Palumbi, 2006). One of the key features of hybrid zones is the rate of change of gene frequency across the zone, and the associated strength of the barrier to gene flow.…”
Section: Introductionmentioning
confidence: 99%
“…These factors need to be taken into account when trying to explain marine clines or estimate population parameters from cline shape. Dispersal-dependent cline theory (also known as tension zone theory; Barton and Hewitt 1985) has recently been promoted as an underused approach for estimating gene flow in marine species with clinal variation (Sotka and Palumbi 2006). Sotka and Palumbi argued that measures of linkage disequilibrium between genetic polymorphisms at indepen-dent loci, when coupled with an estimate of cline width, can be used to generate useful estimates of average gene flow.…”
Section: Implications and Prospects For Further Analysismentioning
confidence: 99%
“…Because larval dispersal will result from a complex interaction between larval behavior and hydrography, the potential for advective forces to accentuate coastal marine clines (Gardner 1997;Sotka and Palumbi 2006) may not be obvious based on the strongest or average oceanographic flow fields along the continental shelf. For example, in an eastern Pacific barnacle (Balanus glandula) allele frequencies shift strikingly over 475 km of coastline despite a capacity for dispersal at an equivalent scale during a 2ϩ week larval stage (Sotka et al 2004).…”
mentioning
confidence: 99%